Cerebral perfusion alterations in patients with trigeminal neuralgia as measured by pseudo-continuous arterial spin labeling - Zhou, Qianling; Li, Meng; Fan, Qisen; Chen, Feng; Jiang, Guihua; Wang, Tianyue; He, Qinmeng; Fu, Shishun; Yin, Yi; Lin, Jinzhi; Yan, Jianhao (Frontiers in Neuroscience, 2022)
Accumulating evidence suggests that trigeminal neuralgia (TN) causes structural and functional alterations in the brain. However, only a few studies have focused on cerebral blood flow (CBF) changes in TN patients. This study aimed to explore whether altered cerebral perfusion patterns exist in TN patients and investigate the relationship between abnormal regional CBF (rCBF) and clinical characteristics of TN. This study included 28 patients with TN and 30 age- and sex-matched healthy controls who underwent perfusion functional MRI of the brain using pseudo-continuous arterial spin labeling in the resting state. The regions of significantly altered CBF in patients with TN were detected using group comparison analyses. Pearson’s correlation analysis was performed to illustrate the relationship between the clinical characteristics and abnormal rCBF. Compared to the control group, TN patients exhibited increased rCBF, primarily in the thalamus, left insula, and bilateral middle frontal gyrus. Furthermore, the CBF values of the thalamus were negatively correlated with pain intensity of TN and positively correlated with pain duration in patients with TN. Primary alterations in rCBF in patients with TN occurred in different brain regions related to pain, which are involved in cognitive-affective interaction, pain perception, and pain modulation. These results indicate that non-invasive resting cerebral perfusion imaging may contribute complementary information to further understanding of the neuropathological mechanism underlying TN.